Investigation of the inhibitory effects of HA-1077 and Y-32885 on the translocation of PKCβI, PKCβII and PKCζ in human neutrophils. Issue 6 (2001) - Siomboing, Xavier; Gressier, Bernard; Dine, Thierry; Brunet, Claude; Luyckx, Michel; Cazin, Michelene; Cazin, Jean-Claude
Abstract : To transmit the information inside the cell, one possibility is the action of an enzyme called kinase that phosphorylates other proteins. To study these enzymes, chemical compound synthesis was needed to know the function and the mechanism of activation. The major difficulty is creating a specific molecule for one kinase. In this study, we test the action of Rho-kinase inhibitors (HA-1077 and Y-32885) on protein kinase C (PKC) in the respiratory burst in the human polymorphonuclear neutrophils. We have shown that these compounds could inhibit the anion superoxide production. To prove their action on PKC, we have shown a decrease of binding of a specific ligand (phorbol-12, 13-dibutyrate) with each inhibitor. During its activation, PKC was translocated from the cytoplasm to the plasmic membrane. We have also shown an inhibition of this translocation, proving an inhibition of PKC by HA-1077 and Y-32885.